Diversity of Mosquitoes Collected from the Southern Areas of Khyber Pakhtunkhwa Pakistan - Khan Niaz Khan; Mohammad Ali; Muhammad Zahid; Wasim Ahmad (Gandhara University, 2022)
OBJECTIVES: The objective of the study was to assess the diversity of mosquitoes in various towns of the southern belt of KPK. METHODOLOGY: This was a descriptive study that was conducted in numerous towns of Western belt of Khyber Pakhtunkhwa. The study areas were Darra Adam Khel, District Kohat, District Karak, District Banu, District D.I. Khan and newly merged districts Mir Ali and Miranshah. From each study site, the samples were collected randomly. The sample collection was done through survey and area visits whereas; the identification process was done in a parasitology laboratory of Hayatabad-Peshawar. Sampling was done from June 2016 to May 2017. RESULTS: A total of 2150 adult mosquitoes were gathered and collected from 42 different locations of the southern belt of KPK and were identified. Based on their identification, 5 genera of the mosquitoes were recognized which were Culex, Anopheles, Psorophora, Aedes and Uranotenia. Culex was found to be most dominant in all the visited areas with a percentage of 12.65 in Miranshah followed by 11.81 in Mirali, 7.16 in Karak, 6.88 in Darra Adam Khel, 6.69 in D.I.Khan, 6.41 in Kohat and 5.11 in Bannu respectively. The results of our findings also revealed the presence of Culex genera in all the habitats and remained the dominant genera among the others followed by Anopheles and Psorophora. Aedes was found in the habitat of plants and grasses etc. whereas Uranotenia was found in marsh/swampy areas as well as in plants/grasses habitat only. CONCLUSION: The outcomes reveal that a climate shifting and extensive urbanization process is enforcing the diversity of mosquitos' fauna in the southern belt of KPK.